Implementation of differentiated learning using a project-based learning model to improve students' mathematical problem-solving ability - Afdillah, Afdillah; Izzati, Nur; Febrian, Febrian (IAIN Palangka Raya, 2024)
This study aimed to determine the difference between students who learn with differentiated Learning by applying the project-based learning model and students who learn by applying the class X expository model on the material of the three-variable equation system. This research uses a quantitative approach with a quasi-experimental type. The data collection techniques used are questionnaires, tests, and observations. The main instrument consisted of questionnaires and test sheets, and supporting instruments consisted of teaching modules and student worksheets. The data analyzed were qualitative data describing learning activities and quantitative data describing pretest and posttest problem-solving ability data in experimental and control classes. The research hypothesis uses the Man Whitney U test; it is found that the mathematical problem-solving ability of students who learn with differentiated Learning using a project-based learning model is higher than that of students who learn with expository with a significance level of 0.05, and the acquisition of a significance value of 0.00.